Prototype of AC Microgrid Solar Power Plant with Off-Grid System - Marhatang, Marhatang; Yunus, A.M Shiddiq; Djalal, Muhammad Ruswandi; Alkautsar, Rifaldi; Caturindah, Winarty (INTEK: Jurnal Penelitian, 2023)
AC microgrid solar power plants can be used as an alternative to overcome the problem of unevenly distributed electricity demand in Indonesia. Prior to implementation, a model or prototype is required to test and provide insights about the solar power plant's functionality as an electric energy generator. The aim of this research was to develop a solar power plant for AC loads and assess the performance of AC Microgrid solar power plants using an Off-grid system. The test results lead to the conclusion that the efficiency of the AC Microgrid solar power plant with the Off-grid system is highly dependent on the intensity of solar radiation, whether it is high or low, striking the panel. The solar panel efficiency ranged from a maximum of 5.54% to a minimum of 4.16%, while the system efficiency varied between a maximum of 8.65% and a minimum of 7.95%.